Comparison of brittleness and flowability between Cipetir Gutta-Percha and commercial Gutta-Percha - Usri, Kosterman; Faza, Yanwar; Sanjaya, Arya; Viona, Nona; Djustiana, Nina; Karlina, Elin; Febrida, Renny; Cahyanto, Arief (Universitas Padjadjaran, 2022)
Introduction: Gutta-Percha (GP) is a standard endodontic filling material found in pure form in the Cipetir area, Indonesia. However, a study comparing physical properties (brittleness and flowability) between pure GP and commercially used GP has not been found. Therefore, this study aims to test the brittleness and flowability of Cipetir GP compared to commercial GP. Methods: This study was quasi-experimental. Forty samples were prepared for each material and test, according to ANSI/ADA specification-GP cones-no 78 in 2006. The first step began by making a sample of Cipetir GP using moulds from a cuvette, commercial GP (Inline #80), and gypsum stone. The second step was to test the brittleness (Crease Recovery Tester) and flowability (according to ADA No. 78 of 2000) of Cipetir GP and commercial GP. Results: The brittleness test of Cipetir GP showed unbroken samples, and the commercial GP showed four broken samples. The Fisher's Exact test showed a p-value of 0.087, which means there was no significant difference in brittleness between Cipetir GP and commercial GP. At the same time, the average value of flowability of Cipetir GP and commercial GP were 6.46 mm and 0.19 mm, respectively. The unpaired t-test showed a p-value<0.05, which means there was a significant difference in the flowability between Cipetir GP and commercial GP. Conclusions: There is a brittleness similarity between Cipetir GP and commercial GP, while the flowability value of Cipetir GP is higher than commercial GP. Those initial findings showed that the Cipetir GP might become an excellent candidate to be an alternative endodontic filling.